“Não é assim mesmo!” : nuances sobre conjugalidades heterossexuais em camadas médias em Cuiabá - Abboudi, Richard Joseph (2019)
This dissertation proposed the realization of a bibliographic research and an ethnographic work seeking to understand and analyze how the mechanisms of conjugality are configured between heterosexual couples of middle classes in Cuiabá within a dynamics of tasks and a routine of activities in a conjugality of their own. It is also about identifying in the speeches possible reproductions of behaviors and concepts that were built, naturalized and incorporated as absolute truths. The intermediate groups of our society formed by the exclusion of the poorest and most affluent layers of the population were classified by Gilberto Velho as middle layers, which are a larger range of subjects who, although classified, may present marked differences and enable the construction of relational analyses loaded from lots of meanings. Even in the most hierarchical societies, there are situations or roles that allow criticism, relativization or even disruption with hierarchy. Recent studies of gender and family, cultural transformations, influence of feminism beyond the individualistic ideal have shown changes in the cultural and social patterns of men and women and their relationships. The feminist achievements of the last 50 years have enabled a new profile for families and gender relations: women as solely responsible for household chores and childcare are subject to questioning and transformation. Seeking to materialize the research, in addition to the ethnographic work, it became necessary a bibliographic survey to predict how the historical evolution of the heterosexual family occurred from the end of the Middle Ages to the present day and how the concept of family has been incorporating new realities and multiple possibilities. We also seek to understand the way the concept of heterosexuality was created as a category from the 19th century, motivated by social and religious issues and strengthened with the creation of the modern state. All forms of social transformation imply reelaborating existing gender and kinship relationships. These relationships are coming to life through multiple possibilities with the deconstruction of relationships and many new "family concepts". These family relationships, by assuming new contours, have driven researchers to broaden the field of their analyses in order to think about the various family dynamics existing in contemporary times, including the notion that the several meanings that involve kinship relationships and theories of condeception and fatherhood have reflected not only facts that we consider "universal and natural", but also somewhat cultural, local and very particular phenomena.